Une méthodologie pour l’enquête sémasiologique - Aline Pons (Lengas)
The maps of linguistic atlases can be either onomasiological (collecting the different local names of the same referent) or semasiological (collecting the different meanings that a lexotype can take on in a given area). Maps of the second type are rarer and are often constructed on the basis of the comparison of several “traditional” linguistic maps, and not through an explicit investigation of word meanings. In the framework of my doctoral thesis, dedicated to the study of the meaning of the Alpine space lexicon in the Cottian Alps, I wanted instead to try to directly investigate the meaning of a selection of lexotypes, singled out from the Linguistic and Ethnographic Atlas of Western Piedmont – ALEPO. To this end, I chose to carry out the investigations in my Occitan variety, in order to free the informants from the burden of translation into a different language, which is articulated in a different taxonomy of the Alpine space. In this contribution, I would like to illustrate the survey methodology I followed.